2010
DOI: 10.1002/jor.21191
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity ultrasound stimulation prevents osteoporotic bone loss in young adult ovariectomized mice

Abstract: Osteoporosis is a disease characterized by low bone mass, increased bone fragility, and a greater risk for bone fracture. Currently, pharmacological intervention can generally aid in the prevention and treatment of osteoporosis, but these therapies are often accompanied by undesirable side effects. Therefore, alternative therapies that minimize side effects are necessary. Biophysical stimuli, especially low-intensity ultrasound stimulation (LIUS), may be potential alternatives to drug-based therapies for osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
3
17
0
1
Order By: Relevance
“…A number of studies have reported an increase in BMD and mechanical strength and stiffness within the initial 7-38 days of US treatment of rabbit tibia (18,42-44). Furthermore, low-intensity ultrasound stimulation in OVX mice is able to activate new bone formation and maintain bone structure, preventing estrogen deficiency-induced bone loss (45). The data presented in the present study suggest that 2 weeks of US and ERT treatment increased the BMD and maximum bone load in OVX rabbits, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have reported an increase in BMD and mechanical strength and stiffness within the initial 7-38 days of US treatment of rabbit tibia (18,42-44). Furthermore, low-intensity ultrasound stimulation in OVX mice is able to activate new bone formation and maintain bone structure, preventing estrogen deficiency-induced bone loss (45). The data presented in the present study suggest that 2 weeks of US and ERT treatment increased the BMD and maximum bone load in OVX rabbits, which is consistent with the results of previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…While our study did not find significant improvements in BV/TV with 30mW/cm 2 US intervention, we observed a significant improvement with 100mW/cm 2 . Our study also supports the findings of Lim et al, who showed that low-intensity US stimulation was capable of preventing bone loss in your adult OVC mice [38]. …”
Section: Discussionsupporting
confidence: 92%
“…Histological analysis using mason tricrome staining showed qualitative improvements in ultrasound treated animals not observed in control groups [29]. In a more recent study, LIPUS (1.5 MHz, 1.0 kHz pulse repetition, 30 mW/cm 2 , with intensity of 200μs pulse length) was applied to 14-week-old OVX mice for 6-week; and indicated that bone volume of treated limb was significantly enhanced compared to the contralateral control [38]. In light of the differences among US stimulation protocols used in these studies, it is remained unclear what role ultrasound signal parameters, in particular signal intensity, play in bone’s response.…”
Section: Introductionmentioning
confidence: 99%
“…Low intensity pulsed US have been used for diagnostic purposes for a long time and been shown to have a positive effect on bone regeneration and fracture healing. 5,12,37 Bone remodeling is a dynamic and continuous process. It has already been shown in different studies that NO modulates fracture healing.…”
Section: Discussionmentioning
confidence: 99%